Design Aplikasi Mobile Sistem Informasi Geografis Panduan Lokasi SPBU - Erick Fernando; A. Raharjo Condrobimo (Teknik Informatika, 2019)
Indonesia is the largest archipelago country in the world consisting of 17,499 islands from Sabang to Merauke. With so many areas in Indonesia that has so many areas scattered and, in every place, has a place for Public Fuel Filling Station (SPBU). With the distribution of gas stations based on regions in Indonesia, information is needed on the existence or position or location of gas stations to facilitate vehicle users to find gas stations. The aim of this research is to develop an application for gas station location instructions so that it can provide detailed information on the position and facilities at the gas station. Application development uses the waterfall approach and uses the Android programming language to build mobile applications. Evaluate application testing with the black box approach, that the application can run in accordance with the functions of each menu on the application so that the application can be used by users. This application can facilitate the user (user) in searching for locations from existing gas stations quickly and precisely and can be accessed by anyone, anytime, and anywhere.